A catalyst for photocatalytic oxidation of formaldehyde, a photocatalytic oxidation formaldehyde flame-retardant thermal insulation aerogel, and a preparation method and application thereof

CN122875265APending Publication Date: 2026-10-09GUANGDONG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611013175.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-08
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]然而,这种气凝胶对于甲醛的去除效果不佳,具体表现为在甲醛浓度为0.5mg/m3时,需要三小时才能净化83%的甲醛

Benefits of technology

[0027]优选地,所述光催化氧化甲醛阻燃保温气凝胶的制备方法中,所述硼酸溶液中,硼酸的浓度为0.2~1wt%。浸泡时间可以为25~40分钟。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875265A_ABST
    Figure CN122875265A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of catalysts, and relates to a catalyst for photocatalytic oxidation of formaldehyde, a formaldehyde photocatalytic oxidation flame-retardant thermal insulation aerogel and a preparation method and application thereof.A catalyst for photocatalytic oxidation of formaldehyde, and a preparation method comprising the following steps: mixing nickel salt, iron salt and silver salt to obtain solution A, mixing NaOH and Na2CO3 to obtain solution B, dissolving solution A and solution B in a polyvinylpyrrolidone solution, adding a MXene suspension, and stirring and reacting; adding a reducing agent, stirring and reacting, to obtain the catalyst for photocatalytic oxidation of formaldehyde.The present application also discloses an aerogel, which has good flame-retardant and thermal insulation properties.Under visible light irradiation, the material exhibits excellent formaldehyde photocatalytic degradation efficiency, can efficiently purify air, and is very suitable for being widely applied to key fields such as building energy-saving reconstruction and indoor air purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst technology, and more specifically, to a catalyst for photocatalytic oxidation of formaldehyde, a flame-retardant and heat-insulating aerogel for photocatalytic oxidation of formaldehyde, its preparation method and application. Background Technology

[0002] Against the backdrop of global low-carbon economic transformation and increasingly stringent building energy efficiency standards, the development of new building insulation materials that combine sustainability, economy, and functionality is of paramount importance. While current mainstream organic insulation materials such as polystyrene and polyurethane occupy a large market share, their resources are limited, and they pose problems such as high flammability and the release of toxic fumes during combustion, causing secondary poisoning. Inorganic insulation materials such as rock wool and glass wool, although possessing flame-retardant properties, suffer from drawbacks such as high hygroscopicity, rapid deterioration of mechanical properties, and high energy consumption during production, contradicting sustainable development and low-carbon goals. Furthermore, existing insulation material systems generally exhibit limited functionality. Facing the synergistic demand of new buildings for "ultra-low thermal conductivity, inherent flame retardancy, and environmental friendliness," there is an urgent need to develop high-performance insulation materials with overall safety through innovation in material structure design, flame-retardant system construction, and material preparation processes. Aerogel, as a novel insulation material, has attracted significant attention due to its ultra-low thermal conductivity and high porosity.

[0003] In building interior environments, besides energy conservation, insulation, and fire safety, indoor environmental safety and human health are equally important considerations. Formaldehyde (HCHO), a toxic and carcinogenic volatile organic compound, primarily originates from building materials, interior furnishings, and adhesives; long-term exposure can cause serious harm to human health. Catalytic degradation of formaldehyde using catalysts is a common approach; however, individual catalyst powders suffer from problems such as easy agglomeration, difficulty in recycling in practical applications, and the potential for dust pollution.

[0004] To address the aforementioned issues, Chinese patent CN121293575A discloses a flame-retardant gel capable of catalytically purifying formaldehyde at room temperature. This gel involves loading manganese oxides onto cellulose powder, then freeze-drying it with sodium alginate in water to obtain a precursor aerogel. The precursor aerogel is then cross-linked by immersing it in a solution containing boric acid and aluminum chloride hexahydrate, followed by freeze-drying to obtain the flame-retardant gel capable of catalytically purifying formaldehyde at room temperature.

[0005] However, this aerogel is not very effective at removing formaldehyde, specifically at a formaldehyde concentration of 0.5 mg / m³. 3 It takes three hours to purify 83% of the formaldehyde. Summary of the Invention

[0006] The purpose of this invention is to overcome the defects and shortcomings of the above-mentioned technical problems and provide a catalyst suitable for photocatalytic oxidation of formaldehyde in the preparation of aerogels, which can improve the degradation rate of formaldehyde through photocatalytic oxidation.

[0007] Another objective of this invention is to provide a photocatalytic oxidation formaldehyde flame-retardant and heat-insulating aerogel.

[0008] The above-mentioned objective of the present invention is achieved through the following technical solution: This invention utilizes a co-precipitation-in-situ reduction method to load a silver / nickel-iron layered double hydroxide (Ag / NiFe-LDH) photocatalyst with photocatalytic formaldehyde oxidation performance onto MXene sheets.

[0009] A catalyst for the photocatalytic oxidation of formaldehyde, the preparation method of which includes the following steps: (1) Mix nickel salt, iron salt and silver salt to obtain solution A, mix NaOH and Na2CO3 to obtain solution B, dissolve solution A and solution B in polyvinylpyrrolidone solution, add MXene suspension to obtain mixed solution, stir reaction to obtain mixed solution containing nickel-iron layered double hydroxide / MXene complex; (2) Add a reducing agent to the mixed solution containing nickel-iron layered double hydroxide / MXene complex in step (1) and stir to react, to obtain the Ag / nickel-iron layered double hydroxide / MXene photocatalytic oxidation catalyst for formaldehyde; In step (1), the molar ratio of nickel salt to iron salt is (2~5):1; the molar ratio of the amount of silver salt to the sum of the amounts of nickel salt and iron salt is (0.05~0.1):1. In the MXene suspension, the mass of MXene is 14-17% of the theoretically generated nickel-iron layered double hydroxide mass; The theoretically generated nickel-iron layered double hydroxide has the general structural formula [Ni 2+ 1-x Fe 3+ x (OH)2] X+ CO3 2- ) X / 2 ·nH2O], where x is calculated from the molar ratio of nickel salt to iron salt in step (1), and 0.17≤x≤0.33, and n is the proportion of water of crystallization, 0≤n≤1.

[0010] MXene (Ti3C2T) x As a novel two-dimensional transition metal carbide / nitride material, it possesses excellent electrical conductivity, abundant surface functional groups (-OH, -O, -F, etc.), and a unique layered structure.

[0011] MXene possesses excellent electrical conductivity and light absorption capabilities, enabling it to act as an electron transport channel to accelerate the transfer of photogenerated carriers, suppress the recombination of photogenerated electron-hole pairs, and improve photocatalytic efficiency. The two-dimensional layered structure of nickel-iron layered double hydroxide (NiFe-LDH) provides a large number of active sites and specific surface area, promoting the separation and transport of photogenerated electron-hole pairs. The Ni / Fe synergistic effect can significantly improve the separation efficiency of photogenerated carriers, and MXene (Ti3C2T) can further enhance this effect. x The Z-scheme heterostructure constructed between Ag / NiFe-LDH and NiFe-LDH effectively promotes the spatial separation of photogenerated electron-hole pairs. Silver nanoparticles extend the visible light response range through surface plasmon resonance (SPR), effectively expanding the visible light response range of the photocatalyst, enhancing light absorption, and promoting the separation of photogenerated electron-hole pairs. Simultaneously, they act as electron transfer bridges to further accelerate charge separation, thereby significantly improving photocatalytic efficiency. The synergistic effect of these three elements endows the Ag / NiFe-LDH / MXene composite photocatalyst with excellent photocatalytic oxidation performance of formaldehyde.

[0012] The photocatalytic mechanism may be as follows: Under visible light irradiation, MXene and NiFe-LDH are simultaneously excited to generate photogenerated electron-hole pairs. Since the Fermi level of Ag nanoparticles lies between MXene and NiFe-LDH, photogenerated electrons in the NiFe-LDH conduction band migrate to the MXene valence band via Ag bridges and recombine with their holes, forming a Z-scheme charge transfer pathway. This results in highly reducing electrons being enriched in the MXene conduction band, while strongly oxidizing holes remain in the NiFe-LDH valence band. The enriched electrons reduce O2 to superoxide radicals (·O2). - ), which is then converted into hydroxyl radicals (·OH); the holes in the valence band of NiFe-LDH directly oxidize H2O / OH. - Formaldehyde molecules are generated by the synergistic action of these reactive oxygen species (ROS) and are gradually oxidized via formic acid intermediates, eventually mineralizing into CO2 and H2O.

[0013] In a specific implementation, the amount of reducing agent added is such that all silver ions are reduced to elemental silver.

[0014] Preferably, in step (1), the preparation method of MXene includes the following steps: reacting LiF, HCl and Ti3AlC2 at 40~45℃ for 36~48 hours, followed by ice bath sonication and centrifugal circulation treatment to obtain MXene.

[0015] Preferably, in step (1), the preparation method of MXene includes the following steps: reacting LiF, HCl and Ti3AlC2 at 40~45℃ for 36~48 hours, sonicating in an ice bath, centrifuging and circulating, sonicating in an ice bath for 20~40 minutes, centrifuging at 3500~4000 rpm for 10~20 minutes to obtain MXene; the concentration of HCl is 9M, and the molar ratio of LiF to Ti3AlC2 is (10~12):1.

[0016] In step (1), in a specific embodiment, the preparation method of MXene includes the following steps: (1) Oil bath etching: LiF powder and hydrochloric acid HCl were added to the reaction vessel, placed in a water bath at 40~45℃, stirred at 500 rpm for 15 min, Ti3AlC2 powder was added, and the reaction was carried out at 40~45℃ for 36~48 hours. (2) Centrifugation and washing: Centrifuge, discard the supernatant, add water and shake well, absorb the white impurities with a paper towel, repeat until pH=7. Start the sonication-centrifugation cycle; sonicate in an ice bath, centrifuge, until the bottom precipitate swells and a thick suspension appears.

[0017] (3) Ultrasonic exfoliation: Ultrasonic bath for 20-40 minutes, centrifuged at 3500-4000 rpm for 10-20 minutes to obtain MXene dispersion. Freeze-dry the dispersion to obtain MXene powder.

[0018] Preferably, in step (1), the molar ratio of the amount of silver salt to the sum of the amounts of nickel salt and iron salt is (0.07~0.1):1.

[0019] The present invention also protects the application of the catalyst for photocatalytic oxidation of formaldehyde as described in any of the above claims in the photocatalytic oxidation of formaldehyde, wherein the wavelength of the light is 420~800 nm.

[0020] This invention also protects a photocatalytic formaldehyde oxidation flame-retardant and heat-insulating aerogel, comprising the catalyst described in any of the above claims for photocatalytic formaldehyde oxidation.

[0021] The present invention also protects the preparation method of the photocatalytic formaldehyde oxidation flame-retardant and heat-insulating aerogel, comprising the following steps: mixing the catalyst for photocatalytic formaldehyde oxidation described above with sodium alginate in water at a mass ratio of (1.5~2.5):1 to obtain a dispersion, freeze-drying to obtain a precursor aerogel; and completely immersing the precursor aerogel in a calcium salt solution and a boric acid solution for cross-linking, freeze-drying to obtain the photocatalytic formaldehyde oxidation flame-retardant and heat-insulating aerogel.

[0022] This invention incorporates boric acid as a crosslinking agent to crosslink with the hydroxyl groups on sodium alginate and MXene, enhancing the flame-retardant effect of the aerogel condensed phase. Simultaneously, calcium ions are introduced to induce the formation of a stable "egg-box" structure gel from the guluronic acid (G units) of sodium alginate. The combination of boric acid and calcium salt produces a double crosslinking effect, strengthening the crosslinking strength between sodium alginate and MXene. Boric acid dehydrates at high temperature to form a glassy B2O3 protective film, which overlaps with the dense carbon layer formed by calcium ion crosslinking, constituting a dual protective system of "glass barrier + dense carbon layer." This results in an aerogel material with a good three-dimensional network structure and excellent flame-retardant, thermal insulation, and photocatalytic properties.

[0023] The double cross-linking treatment not only did not have a negative impact on photocatalytic performance, but also ensured the performance of the catalyst during multiple cycles due to the improved structural stability.

[0024] In a specific embodiment, the freeze-drying temperature can be -20 to -16°C, and the freeze-drying time can be 24 to 30 hours.

[0025] Preferably, in the preparation method of the photocatalytic oxidation of formaldehyde flame-retardant and heat-insulating aerogel, the concentration of sodium alginate in the dispersion is 10~16 mg / ml; and the concentration of catalyst in the dispersion is 20~30 mg / ml.

[0026] Preferably, in the preparation method of the photocatalytic oxidation formaldehyde flame-retardant and heat-insulating aerogel, the concentration of calcium salt in the calcium salt solution is 0.5~3wt%. The soaking time can be 8~15 minutes.

[0027] Preferably, in the preparation method of the photocatalytic oxidation formaldehyde flame-retardant and heat-insulating aerogel, the concentration of boric acid in the boric acid solution is 0.2~1wt%. The soaking time can be 25~40 minutes.

[0028] This invention also protects the application of the photocatalytic oxidation formaldehyde flame-retardant thermal insulation aerogel described in any of the above claims in building insulation materials.

[0029] Compared with the prior art, the beneficial effects of the present invention are: the present invention discloses a catalyst suitable for photocatalytic oxidation of formaldehyde in the preparation of aerogels, which can improve the degradation rate by photocatalytic oxidation of formaldehyde.

[0030] This invention also discloses a photocatalytic oxidation formaldehyde flame-retardant and thermal insulation aerogel, which possesses excellent flame-retardant and thermal insulation properties. Under visible light irradiation, this material exhibits outstanding formaldehyde photocatalytic degradation efficiency, enabling efficient air purification and making it highly suitable for widespread application in key areas such as building energy-saving renovation and indoor air purification. Attached Figure Description

[0031] Figure 1This is a schematic diagram of the self-made photocatalytic formaldehyde purification performance testing device of the present invention.

[0032] Figure 2 The graphs show the formaldehyde purification effect of the photocatalyst powder in Examples 1-3 of this invention over time under light irradiation.

[0033] Figure 3 The graphs show the formaldehyde purification effect of aerogel over time in various embodiments and comparative examples of the present invention.

[0034] Figure 4 X-ray diffraction (XRD) patterns of Ti3AlC2, MXene, NiFe-LDH, NiFe-LDH / MXene, and Ag / NiFe-LDH / MXene powders from Example 1.

[0035] Figure 5 This is a physical image of the ALMAB aerogel from Example 1 of the present invention.

[0036] Figure 6 Fourier transform infrared (FTIR) spectra of the aerogels of Comparative Examples 1-3 and Example 1.

[0037] Figure 7 Thermogravimetric analysis (TGA) diagrams of the ALMAB aerogel of Example 1 and the ALMA aerogel of Comparative Example 3 under nitrogen atmosphere.

[0038] Figure 8 Infrared thermal images of PA aerogel (Comparative Example 1), MA aerogel (Comparative Example 2), ALMA aerogel (Comparative Example 3), and ALMAB aerogel (Example 1) after heating on a heating plate at 75°C for 30 minutes. Detailed Implementation

[0039] To more clearly and completely describe the technical solution of the present invention, the present invention will be further described in detail below through specific embodiments. It should be understood that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the present invention. Various changes can be made within the scope of the claims of the present invention.

[0040] Polyvinylpyrrolidone (PVP), K29-32 (average molecular weight 58,000). Manufacturer: Macklin, CAS No.: 9003-39-8.

[0041] Sodium alginate, content ≥95.0% (T) / ≥98.0% (D-Galacturonic acid sodium salt), manufacturer: Aladdin, CAS No.: 9005-38-3.

[0042] Example 1 1. A catalyst for the photocatalytic oxidation of formaldehyde, the preparation method comprising the following steps: S1. Preparation of MXene, including the following steps: (1) Oil bath etching: 3.2g of lithium fluoride (LiF) powder and 45mL of 9M hydrochloric acid were added to the liner of the polytetrafluoroethylene reactor, placed in a water bath at 45℃, stirred at 500 rpm for 15min, and then 2g of Ti3AlC2 powder (the molar ratio of LiF to Ti3AlC2 was 12:1) was added spoonful by spoonful, and the resulting mixture was reacted at 45℃ for 48 hours.

[0043] (2) Centrifugation washing: Centrifuge at 7000 rpm for 5 min, discard the supernatant, add water and shake well for 1 min, absorb the white impurities with a paper towel, repeat until pH=7. Start sonication-centrifugation cycle: Sonicate in an ice bath for 10 min, centrifuge at 7000 rpm for 3 min, until the bottom precipitate expands and a thick suspension appears.

[0044] (3) Ultrasonic exfoliation: Ultrasonic bath for 30 minutes (add ice cubes halfway through to maintain ice bath environment), centrifuge at 3500 rpm for 15 minutes to obtain MXene dispersion. Freeze-dry the dispersion to obtain MXene powder.

[0045] S2. Preparation of Ag / NiFe-LDH / MXene composite photocatalyst powder: Calculation of the theoretically generated nickel-iron layered double hydroxide mass: When the molar ratio of nickel salt to iron salt is 3:1, the theoretically generated nickel-iron layered double hydroxide has the general structural formula [Ni 0.75 Fe 0.25 (OH)2] 0.25 [(CO3) 0.125 [nH₂O], when n is 0, the theoretical molar mass of the generated nickel-iron layered double hydroxide is 99.50 g / mol. When n is 1, the theoretical molar mass of the generated nickel-iron layered double hydroxide is 117.52 g / mol. When the amount of nickel and iron is 12 mmol, the theoretical mass of the generated nickel-iron layered double hydroxide is 1.19~1.41 g.

[0046] The mass of the actual generated NiFe-LDH was obtained through the following steps: 9 mmol (2.62 g) of nickel nitrate hexahydrate and 3 mmol (1.22 g) of ferric nitrate nonahydrate (Ni:Fe molar ratio 3:1) were dissolved in 50 mL of pure water while stirring to form a homogeneous solution A; 0.02 mol (1.6 g) of NaOH and 0.01 mol (2.12 g) of Na₂CO₃ were dissolved in 50 mL of deionized water to obtain solution B; 3.2 g of PVP was dissolved in 200 mL of deionized water to obtain solution C; solutions A and B were simultaneously added dropwise to solution C to maintain pH ≈ 10, and stirring was continued for 10 minutes, followed by sonication in an ice bath for 15 minutes. The reaction was then carried out at 30 °C under a nitrogen atmosphere for 6 hours with stirring; the mixture was washed three times with deionized water, centrifuged at 7000 rpm for 3 minutes, and the wet precipitate was retained and dried to obtain NiFe-LDH powder. The weight was 1.2 g.

[0047] The theoretically generated nickel-iron layered double hydroxide has a mass of 1.19~1.41g, while the actual generated NiFe-LDH mass is 1.2g. Therefore, it can be deduced that the water of crystallization n in the actually generated nickel-iron layered double hydroxide satisfies 0. <n<0.5。

[0048] (1) Dissolve 9 mmol (2.62 g) nickel nitrate hexahydrate, 3 mmol (1.22 g) ferric nitrate nonahydrate (Ni:Fe molar ratio of 3:1) and 0.19 g (1.12 mmol) silver nitrate (molar ratio of silver salt to the sum of nickel and iron salts of 0.093:1) in 50 mL of pure water while stirring to form a homogeneous solution A; dissolve 0.02 mol (1.6 g) NaOH and 0.01 mol (2.12 g) Na2CO3 in 50 mL of deionized water to obtain solution B; dissolve 3.2 g PVP was dissolved in 200 mL of deionized water to obtain solution C; 0.2 g of MXene powder (the mass of MXene is 14.2~16.8% of the theoretically generated nickel-iron layered double hydroxide) was added to 20 mL of deionized water and sonicated in an ice bath for 10 min to disperse it and obtain an MXene suspension. Solutions A and B were simultaneously added dropwise to solution C to maintain pH≈10. After adding the MXene suspension, a mixed solution was obtained. The mixture was stirred for 10 minutes and then sonicated in an ice bath for 15 minutes. The mixture was stirred and reacted at 30 °C under a nitrogen atmosphere for 6 hours to obtain a mixed solution containing nickel-iron layered double hydroxide / MXene complex. Wash three times with deionized water, centrifuge at 7000 rpm for 3 min, retain the wet precipitate (do not dry), add 50 mL of deionized water to the wet precipitate, and sonicate in an ice bath for 7 min to form a uniform suspension (adjust with NaOH and maintain pH≈8.5). (2) In step (1), 0.247 g of a 15 mL solution prepared with 1.4 mmol of ascorbic acid was added dropwise to the mixed solution containing nickel-iron layered double hydroxide / MXene complex. The pH was retested and found to be 9. The solution was stirred for 2.5 hours at 30°C under a nitrogen atmosphere in the dark (at this time, the wet colloidal dispersion is good and the ascorbic acid can fully contact Ag). + The sample was washed three times with deionized water to remove excess ascorbic acid and dehydrogenation products. After freeze-drying, the Ag / nickel-iron layered double hydroxide / MXene photocatalyst for the oxidation of formaldehyde, abbreviated as 14AgNFL / MXene powder, was obtained, weighing 1.5208g.

[0049] 2. A photocatalytic oxidation formaldehyde flame-retardant and heat-insulating aerogel, the preparation method of which includes the following steps: (1) Dispersion and mixing: Disperse 0.4g of the prepared 14AgNFL / MXene powder in 15mL of deionized water (concentration of 26.67mg / ml), stir magnetically for 10 minutes to ensure uniform dispersion, and then sonicate for 10 minutes. Then add 0.2g of sodium alginate (SA) with a concentration of 13.3mg / ml. The mass ratio of the photocatalytic oxidation catalyst to sodium alginate is 2:1. Continue to stir magnetically for 1.5h until the sodium alginate is completely dissolved.

[0050] (2) Ultrasonic homogenization: The above mixed dispersion was ultrasonically treated for 20 minutes, and then thoroughly stirred to room temperature to ensure that the system is uniform and stable.

[0051] (3) Pre-freezing of molds: Pour the uniformly dispersed liquid into the mold, let it stand and then unmold it. Invert the mold and put it in the freezer for half an hour (temperature about -18℃).

[0052] (4) Freeze-drying: Place the pre-frozen sample into a vacuum freeze dryer and freeze-dry for more than 24 hours to obtain the intermediate aerogel product 14AgNFL / MXene-SA.

[0053] (5) Double cross-linking curing: The intermediate aerogel was subjected to the following soaking treatments in sequence: first, it was immersed in a 1wt% calcium chloride solution for 10 minutes, so that Ca 2+ The carboxyl groups of sodium alginate are chelated and crosslinked to form an "egg box" structure; then it is immersed in a 0.5wt% boric acid solution for 30 minutes to allow the borate ions to crosslink with the hydroxyl groups on the surface of sodium alginate and MXene; after removal, it is washed once with deionized water to remove residual crosslinking agent.

[0054] (6) Post-treatment drying: The cross-linked sample was freeze-dried again at -18℃ for 24h, and then subjected to appropriate ultrasonic treatment and finishing to obtain the final 14AgNFL / MXene-SA-B photocatalytic flame retardant thermal insulation aerogel (ALMAB aerogel for short).

[0055] Example 2 A photocatalyst for the oxidation of formaldehyde was prepared in a method different from that in Example 1. In step (1), the amount of silver nitrate added was changed to 0.149 g and 0.88 mmol (the molar ratio of the amount of silver salt to the sum of the amounts of nickel salt and iron salt was 0.073:1). In step (2), the amount of ascorbic acid added was changed to 0.194 g and 1.1 mmol. The amounts of other raw materials and operating conditions were completely consistent, resulting in 11 AgNFL / MXene powder weighing 1.4949 g.

[0056] A photocatalytic oxidation formaldehyde flame-retardant and heat-insulating aerogel is prepared in a way that differs from that in Example 1 in that it uses the above-mentioned 11AgNFL / MXene photocatalytic oxidation formaldehyde catalyst.

[0057] Example 3 A photocatalyst for the oxidation of formaldehyde was prepared in a method different from that in Example 1. In step (1), the amount of silver nitrate added was changed to 0.109 g and 0.64 mmol (the molar ratio of the amount of silver salt to the sum of the amounts of nickel salt and iron salt was 0.053:1). In step (2), the amount of ascorbic acid added was changed to 0.141 g and 0.8 mmol. The amounts of other raw materials and operating conditions were completely the same, resulting in 8 AgNFL / MXene powder weighing 1.4690 g.

[0058] A photocatalytic oxidation formaldehyde flame-retardant and heat-insulating aerogel is prepared in a method that differs from that in Example 1 in that it uses the above-mentioned 8AgNFL / MXene photocatalytic oxidation formaldehyde catalyst.

[0059] Comparative Example 1: Pure sodium alginate-based aerogel (PA aerogel) An aerogel is prepared as follows: 0.2g of sodium alginate is added to 15mL of deionized water and stirred until completely dissolved. The solution is poured into a mold, pre-frozen at -18℃, and then freeze-dried under vacuum for 24h to obtain pure sodium alginate-based aerogel (PA aerogel).

[0060] Comparative Example 2MXene-Sodium Alginate Aerogel (MA Aerogel) An aerogel, the preparation method of which differs from that of Example 1 is as follows: (1) 0.4g of MXene powder is dispersed in 15mL of deionized water, and 0.2g of sodium alginate is added and stirred until completely dissolved to obtain MXene-sodium alginate aerogel (MA aerogel).

[0061] Comparative Example 3: 14AgNFL / MXene-SA aerogel (ALMA aerogel) without post-crosslinking An aerogel, the preparation method of which includes the following steps: (1) Dispersion and mixing: Disperse 0.4g of 14AgNFL / MXene powder in 15mL of deionized water (concentration of 26.67mg / ml), stir magnetically for 10 minutes to ensure uniform dispersion, and then sonicate for 10 minutes. Then add 0.2g of sodium alginate (SA) with a concentration of 13.3mg / ml, and continue to stir magnetically for 1.5h until the sodium alginate is completely dissolved.

[0062] (2) Ultrasonic homogenization: The above mixed dispersion was ultrasonically treated for 20 minutes, and then thoroughly stirred to room temperature to ensure that the system is uniform and stable.

[0063] (3) Pre-freezing of molds: Pour the uniformly dispersed liquid into the mold, let it stand and then unmold it. Invert the mold and put it in the freezer for half an hour (temperature about -18℃).

[0064] (4) Freeze-drying: Place the pre-frozen sample into a vacuum freeze dryer and freeze-dry for more than 24 hours to obtain the intermediate aerogel product 14AgNFL / MXene-SA.

[0065] Uncrosslinked 14AgNFL / MXene-SA aerogel (ALMA aerogel) was obtained.

[0066] Comparative Example 4 A photocatalyst for the oxidation of formaldehyde was prepared in a method different from that in Example 1, in step (1), the amount of silver nitrate added was changed to 0.231 g and 1.36 mmol (the molar ratio of the amount of silver salt to the sum of the amounts of nickel salt and iron salt was 0.113:1). In step (2), the amount of ascorbic acid added was changed to 0.299 g and 1.7 mmol, while the amounts of other raw materials and operating conditions remained completely the same, resulting in 17AgNFL / MXene powder.

[0067] A photocatalytic oxidation formaldehyde flame-retardant and heat-insulating aerogel is prepared in a method that differs from that in Example 1 in that it uses the above-mentioned 17AgNFL / MXene photocatalytic oxidation formaldehyde catalyst.

[0068] Performance testing (1) Photocatalytic formaldehyde purification performance test The formaldehyde purification performance test was conducted in a self-made experimental apparatus (the structure of the experimental apparatus is as follows). Figure 1As shown in the figure, the main body of the experimental setup is a sealed box with a volume of approximately 10L. Inside the box, there is a formaldehyde detector that can display the formaldehyde concentration in real time, a small fan that promotes gas flow inside the box, a simulated sunlight source (300W xenon lamp with a 420 nm cutoff filter), and a device for storing aerogel material. This storage device has good sealing properties, which can prevent the aerogel material from contacting formaldehyde before the test begins. After the formaldehyde concentration inside the device stabilizes, the aerogel material in the experimental setup can then be allowed to fully contact the formaldehyde in the sealed box. During the test, the environment inside the sealed box is not affected by external factors.

[0069] 0.1 g of each of the catalysts from Examples 1-3 and Comparative Example 4 were placed in a sealed photocatalytic reaction apparatus (approximately 10 L in volume), and formaldehyde gas was introduced to achieve an initial concentration of approximately 2 ppm (2.46 mg / m³). 3 After 30 minutes of adsorption equilibrium in the darkroom, a simulated sunlight source (300 W xenon lamp with a 420 nm cutoff filter) was turned on, and formaldehyde concentration was measured every 5 minutes for 60 minutes. The test results are as follows: Figure 2 As shown.

[0070] The formaldehyde removal efficiency of the sample is evaluated according to the following formula: D=(C0-C) / C0×100%, where: D is the formaldehyde removal efficiency (%); C0 is the initial mass concentration of formaldehyde (ppm); and C is the mass concentration of formaldehyde (ppm) after different reaction times.

[0071] Depend on Figure 2 It can be seen that formaldehyde degradation initially increases and then decreases with increasing Ag loading. Specifically, the 1-hour formaldehyde degradation rate is 78% for 8AgNFL / MXene, 85% for 11AgNFL / MXene, and reaches a maximum of 91% for 14AgNFL / MXene. However, when the Ag loading is further increased to 17AgNFL / MXene, the degradation rate decreases to 72%. This may be because, within the lower Ag loading range, as the Ag content increases, the surface plasmon resonance (SPR) effect of Ag nanoparticles is enhanced, the visible light absorption range expands, the photogenerated carrier separation efficiency improves, and the photocatalytic activity gradually increases. However, when the Ag loading exceeds the optimal value, excessive Ag nanoparticles aggregate on the NiFe-LDH surface, obscuring some active sites and producing a light-shielding effect, leading to a decrease in photocatalytic activity.

[0072] Before the experiment, the formaldehyde detector was placed and the fan was turned on. About 0.4g of aerogel material was placed in the storage device and sealed. 1.2 μL of HCHO (15wt%) was injected into the sealed box to stabilize the formaldehyde concentration in the sealed box at about 2ppm. Then the lid of the storage device was opened to allow the aerogel material in the device to fully contact the formaldehyde in the box. The changes in the formaldehyde detector reading were observed, and the trend of formaldehyde concentration change in the sealed box was recorded over 3 hours.

[0073] The formaldehyde removal efficiency of the sample is evaluated according to the following formula: D=(C0-C) / C0×100%, where: D is the formaldehyde removal efficiency (%); C0 is the initial mass concentration of formaldehyde (ppm); and C is the mass concentration of formaldehyde (ppm) after different reaction times.

[0074] Figure 3 (a) is a graph showing the change in formaldehyde purification effect over time under light conditions for ALMAB aerogel of Example 1, ALMA aerogel of Comparative Example 3, MA aerogel of Comparative Example 2, and PA aerogel of Comparative Example 1.

[0075] Figure 3 (b) in the figure is a graph showing the change of formaldehyde purification effect of ALMAB aerogel in Example 1 and MA aerogel in Comparative Example 2 over time under light and dark conditions.

[0076] Figure 3 (c) in the figure is a graph showing the change of formaldehyde purification effect of ALMAB aerogel under light conditions in Examples 1-3 of the present invention over time.

[0077] from Figure 3 It can be seen that under dark conditions (no light) for 3 hours, the formaldehyde removal rate of each aerogel sample was less than 90%, mainly due to the physical adsorption effect of the porous structure of the aerogel. After visible light irradiation, the formaldehyde removal rate of MA aerogel in Comparative Example 2 was approximately 50%, mainly attributed to the light absorption of MXene itself and a small amount of photocatalytic activity. The 3-hour photocatalytic formaldehyde degradation rates of ALMAB aerogels in Examples 1, 2, and 3 were 85.0%, 91.5%, and 98%, respectively, indicating that the aerogels have good photocatalytic activity.

[0078] (2) Powder XRD characterization: The Ag / NiFe-LDH / MXene powder and its intermediate products prepared in Example 1 were characterized by XRD. Figure 4 As shown in (a), the Ti3AlC2 raw material exhibits a characteristic diffraction peak at 2θ≈39°. This peak disappears after LiF / HCl etching, and the (002) crystal plane diffraction peak of MXene shifts to approximately 7°, indicating that the Al layer was successfully etched and MXene was successfully prepared. Figure 4As shown in (b), the NiFe-LDH / MXene exhibits characteristic diffraction peaks of the (003) crystal plane of NiFe-LDH at approximately 11.5°, confirming the successful loading of NiFe-LDH onto the MXene sheets. The 14AgNFL / MXene sample shows new diffraction peaks at 2θ≈38°, 44°, and 64°, corresponding to the (111), (200), and (220) crystal planes of face-centered cubic Ag, respectively, indicating that Ag… + Successfully restored to Ag in situ 0 Nanoparticles. With increasing Ag loading, the intensity of Ag diffraction peaks gradually increased, while the characteristic peaks of LDH changed slightly, indicating that the introduction of Ag nanoparticles had little impact on the crystal structure of NiFe-LDH, and the Ag / NiFe-LDH / MXene composite structure was successfully constructed.

[0079] (3) Aerogel density measurement: The actual ALMAB aerogel of Example 1 is shown in Figure 1. Figure 5 As shown, it exhibits a complete block structure with uniform color and no obvious cracks on the surface. Calculated using the formula ρ=m / v, the average density of the ALMAB aerogel in Example 1 is approximately 45.3 mg / cm³. 3 It possesses lightweight properties, meeting the lightweight requirements of building insulation materials. Furthermore, the ALMAB aerogel in Example 1 also exhibits good shape plasticity and structural stability.

[0080] (4) FTIR spectroscopy analysis The ALMAB aerogel of Example 1, the ALMA aerogel of Comparative Example 3, the MA aerogel of Comparative Example 2, and the PA aerogel of Comparative Example 1 were tested using Fourier transform infrared spectroscopy with the KBr pellet method. The test results are as follows: Figure 6 As shown.

[0081] The four curves are at 3200–3600 cm. -1 Broad and strong absorption bands appear throughout the range, attributed to the stretching vibrations of the -OH group, mainly originating from the abundant hydroxyl groups on the sodium alginate molecular chain and the oxygen-containing functional groups such as -OH, -O, and -F on the MXene surface. Among them, MA, ALMA, and ALMAB show absorption bands at 3428 cm⁻¹. -1 The nearby -OH stretching vibration peak is enhanced compared to PA, attributed to the enhanced hydrogen bond interactions due to the introduction of MXene. At 2919 cm⁻¹ -1 and 2838 cm -1 Nearby, both symmetric and asymmetric stretching vibration peaks of CH were observed, attributed to the methylene group in the sodium alginate framework. (1600 cm⁻¹) -1 and 1420 cm -1 The characteristic peaks nearby correspond to COO, respectively. -The asymmetric and symmetric stretching vibrations confirmed the presence of the carboxyl group in sodium alginate.

[0082] Comparing PA (black curve) and MA (red curve), MA is at 560 cm. -1 The appearance of new absorption peaks on both sides, attributed to the Ti-O characteristic vibration of MXene, indicates that MXene has been successfully introduced into the aerogel system. Further comparison of MA and ALMA (blue curves) shows that ALMA has a peak at 650 cm⁻¹. -1 New characteristic peaks appear on both sides, attributed to the stretching vibrations of the Ni-O coordination bonds, and at 480 cm⁻¹... -1 The vibrations of nearby Fe-O coordination bonds were also enhanced, indicating that NiFe-LDH had been loaded onto MXene and successfully introduced into the aerogel system; the introduction of Ag also led to increased vibrations at 550–750 cm⁻¹. -1 The vibrational peak intensity of the metal-oxygen bond (MO) is significantly enhanced within the range.

[0083] Further comparison of ALMA and ALMAB (green curves) revealed several significant changes in the spectrum of ALMAB after calcium ion-boric acid double crosslinking treatment: at approximately 3225 cm⁻¹... -1 A distinct β-OH stretching vibration peak appears at approximately 1438 cm⁻¹. -1 An enhanced BO characteristic absorption peak appears at approximately 1334 cm⁻¹; -1 A new absorption peak belonging to the BOC bond appears at approximately 1196 cm⁻¹. -1 A BO ​​vibration peak appeared at [location missing]. The appearance of these new peaks indicates that boric acid underwent a cross-linking reaction with the hydroxyl groups on the surface of sodium alginate and MXene, forming a BOC bond structure. Furthermore, at 1600 cm⁻¹... -1 and 1415 cm -1 The vicinity belongs to COO - The vibrational peaks of Ca2+ were enhanced and slightly shifted to lower wavenumbers after crosslinking, which is attributed to the fact that Ca2+... 2+ A stable "eggbox" structure was formed through chelation with the carboxyl groups in the sodium alginate G unit. These results fully demonstrate the successful construction of the calcium ion-boronic acid double crosslinked network in the ALMAB aerogel.

[0084] (5) Thermogravimetric analysis (TGA) test The thermal stability of ALMA aerogel (Comparative Example 3) and ALMAB aerogel (Example 1) was tested using a thermogravimetric analyzer. The thermogravimetric analysis was performed at a temperature range of room temperature to 700°C, a heating rate of 20°C / min, and a nitrogen atmosphere. The results are shown below. Figure 7 As shown.

[0085] Depend on Figure 7It can be seen that both curves show slight mass loss before 100℃, mainly attributed to the evaporation of adsorbed water in the sample. The ALMA aerogel of Comparative Example 3 exhibits significant thermal weight loss starting at approximately 220℃, with a sharp decrease in mass within the 220–280℃ range. This is mainly due to the thermal decomposition of the sodium alginate polymer chains and the removal of water from the NiFe-LDH interlayer. Subsequently, it shows a slow weight loss trend in the 280–700℃ range, with a residual mass of approximately 37% at 700℃. The ALMAB aerogel of Example 1, based on ALMA, incorporates boric acid and calcium chloride as dual crosslinking agents. Its initial thermal decomposition temperature is delayed to approximately 250℃, and the weight loss rate is significantly slowed in the 250–380℃ range, resulting in a smoother overall thermal degradation curve. At 700℃, the residual mass of the ALMAB aerogel of Example 1 increases to approximately 45%, about 8 percentage points higher than that of the ALMA aerogel of Comparative Example 3.

[0086] The above results demonstrate that the calcium ion-boric acid double crosslinking structure effectively enhances the thermal decomposition resistance of the aerogel: on the one hand, the glassy B2O3 protective film formed by the dehydration of boric acid at high temperatures can form a physical thermal barrier on the material surface, preventing heat transfer to the interior; on the other hand, the "egg-box" crosslinking structure formed by calcium ions and sodium alginate carboxyl groups improves the thermal stability of the polymer backbone and promotes the formation of a dense carbon layer. The synergistic effect of the glassy protective layer and the dense carbon layer significantly suppresses the mass loss of the aerogel at high temperatures, endowing ALMAB aerogel with superior heat resistance.

[0087] (6) Flame retardant performance test - Limiting oxygen index (LOI) The combustion performance of ALMAB aerogel from Example 1, ALMA aerogel from Comparative Example 3, MA aerogel from Comparative Example 2, and PA aerogel from Comparative Example 1 was tested using a fully automated oxygen index analyzer. The test standard was GB / T 2406.2-2009 "Determination of Combustion Behavior by Oxygen Index Method for Plastics - Part 2: Room Temperature Test". The test was conducted using a top-side combustion method, with sample dimensions of 100×10×10 mm. The test results are shown in Table 1 below.

[0088]

[0089] Table 1 shows that the limiting oxygen index (LOI) of PA aerogel in Comparative Example 1 and ALMA aerogel in Comparative Example 3 are 21.0 and 22.5, respectively, which fall into the category of flammable materials, indicating that the flame retardant properties of the uncrosslinked aerogel are poor. The MA aerogel in Comparative Example 2, due to the introduction of MXene and calcium ion-boric acid crosslinking, has an LOI of 23.5, indicating improved flame retardancy. The ALMAB aerogel in Example 1, after calcium ion-boric acid double crosslinking treatment, achieves a limiting oxygen index of 36.3, classifying it as a flame-retardant material, with significantly better flame retardant properties than the comparative examples. This demonstrates that the synergistic effect of MXene, Ag / NiFe-LDH, and the calcium ion-boric acid double crosslinking system endows the aerogel with excellent condensed-phase flame retardant capabilities.

[0090] (7) Vertical burning test (UL-94) Vertical flammability tests were conducted on the ALMAB aerogel of Example 1, the ALMA aerogel of Comparative Example 3, the MA aerogel of Comparative Example 2, and the PA aerogel of Comparative Example 1, according to the UL-94 standard. The sample size was 125 mm × 13 mm × thickness, with 5 parallel samples per group. The test results showed that the PA aerogel of Comparative Example 1 continued to burn after ignition with dripping, and received no UL-94 rating; the ALMA aerogel of Comparative Example 3, although without dripping, had a longer burning time and was rated V-2; the MA aerogel of Comparative Example 2 had a shorter burning time and was rated V-1; the ALMAB aerogel of Example 1 burned for less than 10 seconds after both ignitions, without dripping, and formed a complete expanded char layer after combustion, achieving the highest flame retardant rating, V-0. This result indicates that the calcium ion-boric acid double crosslinking system combined with MXene and Ag / NiFe-LDH components endows the aerogel with excellent flame retardant and fire-resistant properties.

[0091] (8) Thermal insulation performance test The thermal insulation performance of ALMAB aerogel in Example 1, ALMA aerogel in Comparative Example 3, and MA aerogel in Comparative Example 2 was tested using a TC3000E thermal conductivity meter. The thermal conductivity test conditions were: ambient temperature 15℃, sample size 40×60×5mm. After placing the experimental samples, the test began when the temperature fluctuation was ≤±0.1℃ within 10 minutes. Each test consisted of 3 trials, with a 3-minute interval between each trial. Five sets of data were collected using different samples, and the average value was calculated. The test results are shown in Table 2 below.

[0092]

[0093] The thermal conductivity of the ALMAB aerogel in Example 1, the ALMA aerogel in Comparative Example 3, and the MA aerogel in Comparative Example 2 are 37.2, 39.2, and 38.5 mW / (m·K), respectively, all within the ultra-low thermal conductivity range. The thermal conductivity of the MA aerogel in Comparative Example 2 and the ALMAB aerogel in Example 1 is slightly lower than that of the ALMA aerogel in Comparative Example 3. This is attributed to the more dense and uniform three-dimensional network structure formed by the calcium ion-boric acid double crosslinking, which effectively suppresses gas-phase heat transfer.

[0094] To further demonstrate the heat insulation effect, an infrared thermal imager was used to test the surface temperature distribution of four aerogels—PA aerogel (Comparative Example 1), MA aerogel (Comparative Example 2), ALMA aerogel (Comparative Example 3), and ALMAB aerogel (Example 1)—after heating them on a 75°C heating plate for 30 minutes. The test results are as follows: Figure 8 As shown. By Figure 8 It can be seen that the PA aerogel in Comparative Example 1 has the highest surface temperature of 45.1℃, indicating the worst thermal insulation effect. The MA aerogel in Comparative Example 2 has a surface temperature that drops to 40.0℃, indicating that the introduction of MXene and its layered stacking structure have a certain blocking effect on heat transfer. The ALMA aerogel in Comparative Example 3 has a surface temperature of 41.5℃, slightly higher than MA, which is attributed to the introduction of Ag / NiFe-LDH / MXene photocatalyst powder increasing the solid-phase heat transfer path. The ALMAB aerogel in Example 1 has the lowest surface temperature, at only 38.2℃, which is about 6.9℃ lower than PA and significantly lower than the MA aerogel in Comparative Example 2 and the ALMA aerogel in Comparative Example 3. The excellent thermal insulation performance of the ALMAB aerogel in Example 1 is mainly due to the more dense and uniform three-dimensional network structure constructed by the calcium ion-boric acid double crosslinking treatment, which effectively inhibits the gas refluxing and the heat conduction of the solid skeleton. At the same time, the layered barrier effect of MXene and the high porosity and low density characteristics of the aerogel work together to play a thermal shielding role. The above results directly demonstrate that ALMAB aerogel has excellent thermal insulation properties.

[0095] In summary, the preparation method of the flame-retardant and heat-insulating aerogel for photocatalytic formaldehyde degradation of the present invention utilizes a double crosslinking system of calcium ions and boric acid to load Ag / NiFe-LDH photocatalyst onto MXene and then react it with sodium alginate to prepare a three-dimensional aerogel material. Under visible light irradiation, this material can efficiently utilize light energy to excite the Ag / NiFe-LDH / MXene composite photocatalyst to generate photogenerated electron-hole pairs. Through the synergistic effect of the MXene / NiFe-LDH Z-scheme heterojunction and the SPR effect of Ag nanoparticles, the photocatalytic degradation efficiency of low-concentration formaldehyde in a room temperature environment is significant, and the photocatalytic stability is excellent. Furthermore, the aerogel preparation avoids the problems of catalyst powder agglomeration, difficulty in recycling, and dust pollution. In addition, the aerogel of the present invention has excellent flame retardant properties and thermal insulation capabilities. Its vertical combustion rating reaches V-0, its limiting oxygen index is over 35%, and its thermal conductivity is as low as 39.4 mW / (m·K). It can be widely used in building insulation materials to achieve high-efficiency continuous catalytic purification of indoor formaldehyde driven by visible light at room temperature.

[0096] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A catalyst for the photocatalytic oxidation of formaldehyde, characterized in that, The preparation method includes the following steps: (1) Mix nickel salt, iron salt and silver salt to obtain solution A, mix NaOH and Na2CO3 to obtain solution B, dissolve solution A and solution B in polyvinylpyrrolidone solution, add MXene suspension to obtain mixed solution, stir reaction to obtain mixed solution containing nickel-iron layered double hydroxide / MXene complex; (2) Add a reducing agent to the mixed solution containing nickel-iron layered double hydroxide / MXene complex in step (1) and stir to react, to obtain the Ag / nickel-iron layered double hydroxide / MXene photocatalytic oxidation catalyst for formaldehyde; In step (1), the molar ratio of nickel salt to iron salt is (2~5):1; the molar ratio of the amount of silver salt to the sum of the amounts of nickel salt and iron salt is (0.05~0.1):

1. In the MXene suspension, the mass of MXene is 14-17% of the theoretically generated nickel-iron layered double hydroxide mass; The theoretically generated nickel-iron layered double hydroxide has the general structural formula [Ni 2+ 1-x Fe 3+ x (OH)2] X+ CO3 2- ) X / 2 ·nH2O], where x is calculated from the molar ratio of nickel salt to iron salt in step (1), and 0.17≤x≤0.33, and n is the proportion of water of crystallization, 0≤n≤1.

2. The catalyst for photocatalytic oxidation of formaldehyde according to claim 1, characterized in that, In step (1), the preparation method of MXene includes the following steps: reacting LiF, HCl and Ti3AlC2 at 40~45℃ for 36~48 hours, followed by ice bath sonication and centrifugal circulation treatment to obtain MXene.

3. The catalyst for photocatalytic oxidation of formaldehyde according to claim 1, characterized in that, In step (1), the molar ratio of the amount of silver salt to the sum of the amounts of nickel salt and iron salt is (0.07~0.1):

1.

4. The application of the catalyst for photocatalytic oxidation of formaldehyde according to any one of claims 1 to 3 in the photocatalytic oxidation of formaldehyde, characterized in that, In this application, the wavelength of light is 420~800 nm.

5. A photocatalytic formaldehyde oxidation flame-retardant and heat-insulating aerogel, characterized in that, The catalyst for photocatalytic oxidation of formaldehyde as described in any one of claims 1 to 3 is included.

6. The preparation method of the photocatalytic oxidation formaldehyde flame-retardant and heat-insulating aerogel according to claim 5, characterized in that, The process includes the following steps: mixing the catalyst for photocatalytic oxidation of formaldehyde according to any one of claims 1 to 3 with sodium alginate in water at a mass ratio of (1.5 to 2.5):1 to obtain a dispersion, freeze-drying to obtain a precursor aerogel; and then completely immersing the precursor aerogel in a calcium salt solution and a boric acid solution for cross-linking, followed by freeze-drying to obtain the photocatalytic oxidation of formaldehyde flame-retardant and heat-insulating aerogel.

7. The preparation method of the photocatalytic oxidation formaldehyde flame-retardant and heat-insulating aerogel according to claim 6, characterized in that, The concentration of sodium alginate in the dispersion is 10-16 mg / ml; the concentration of catalyst in the dispersion is 20-30 mg / ml.

8. The preparation method of the photocatalytic oxidation formaldehyde flame-retardant and heat-insulating aerogel according to claim 6, characterized in that, The concentration of calcium salt in the calcium salt solution is 0.5~3wt%.

9. The preparation method of the photocatalytic oxidation formaldehyde flame-retardant and heat-insulating aerogel according to claim 6, characterized in that, The concentration of boric acid in the boric acid solution is 0.2~1wt%.

10. The application of the photocatalytic oxidation formaldehyde flame-retardant thermal insulation aerogel according to any one of claims 6 to 9 in building insulation materials.

Citation Information

Patent Citations

  • Flame-retardant aerogel capable of catalytically purifying formaldehyde at room temperature as well as preparation method and application of flame-retardant aerogel

    CN121293575A